ReACanROC: Towards the creation of a France–Canada research network for out-of-hospital cardiac arrest. (July 2020) - Heidet, Matthieu; Fraticelli, Laurie; Grunau, Brian; Cheskes, Sheldon; Baert, Valentine; Vilhelm, Christian; Hubert, Hervé; Tazarourte, Karim; Vaillancourt, Christian; Tallon, John; Christenson, Jim; El Khoury, Carlos; et al.
Abstract: Aims: There are large differences between emergency medical systems, which may account for variability in outcomes. We seek to compare prehospital organizations, response modes, patient characteristics and outcomes after out-of-hospital cardiac arrest, between France and Canada, and discuss the need for the first European–North American prehospital research network on out-of-hospital cardiac arrest. Methods: Preliminary comparative description of data drawn from two nation-wide, population-based, Utstein-style prospectively implemented registries for out-of-hospital cardiac arrest in France and Canada (France: RéAC, Canada: CanROC), covering approximately 80 million people, and soon to be participating in an international research network in 2020. Results: Since creation, 103, 722 cases were included in France and approximately 99, 317 in Canada. Data used in this work were drawn from 2011 to 2016, and comprised around 33, 688 adult, non-traumatic, treated cases in Canada, and 55, 358 in France, leading to estimated incidence rates of 75.3/100, 000 inhabitants in France and 83/100, 000 in Canada. In both countries, out-of-hospital cardiac arrest predominantly occurred in male patients, in their late sixties, at home, of presumed cardiac aetiology. Bystander cardiopulmonary resuscitation was provided in half of the cases. First assessed cardiac rhythm was shockable in 16% (France) vs. 22% (Canada). Professional resuscitation was attempted in 82% (France) and 60% (Canada). Prehospital organizations and response modes differed in the constitution of responding teams (France: physician-led advanced life support, Canada: trained paramedics), in response time intervals (call to first professional responders' arrival at scene 6.5 min (interquartile range IQR [5.2–8.3]) (Canada) vs. 10 min [7–15] (France)), in on-scene interventions, type of referral at hospital (France: systematic bypass of emergency department, tertiary hospital first, Canada: occasional bypass, mainly closest hospital first), and in outcomes (overall survival at hospital discharge in France: 5% vs. Canada: 11%). Conclusion: Despite similarities in some out-of-hospital cardiac arrest Utstein variables, several differences exist between French and Canadian prehospital systems, and ultimately, between outcomes. The creation of the ReACanROC research network will facilitate the conduction of further analyses to better understand predictors of this variability.